Differences in trampoline-related knee injuries between children and adults: a cross-sectional study - Husen, Martin; Engrav, Samantha K.; Saul, Dominik; Stuart, Michael J.; Milbrandt, Todd A.; Levy, Bruce A.; Krych, Aaron J.; Saris, Daniël B.F. (Orthopaedic journal of sports medicine, 2023)
Background: Little is known about the specific risk of knee injuries due to trampoline accidents in adults compared with children. - Purpose: To investigate the differences in trampoline-related knee injuries between children and adults and identify risk factors and protective strategies to reduce injury incidence. - Study Design: Cross-sectional study; Level of evidence, 3. - Methods: Data on 229 consecutive patients treated for trampoline-related knee injuries in a single institution were prospectively collected, analyzed, and included. Risk factors, injury patterns, and clinical treatments were compared between skeletally immature and skeletally mature patients. Logistic regression was used to determine the odds ratios for specific risk factors for trampoline-related injuries—including body mass index (BMI), trauma mechanism, patient age, and accident location. - Results: A total of 229 patients met the inclusion criteria; 118 (52%) patients (women, 54.2%; mean age, 8.5 ± 4.1 years) were skeletally immature at the time of injury, and 111 (48%) patients (women, 72%; mean age, 31.9 ± 13.1 years) had closed physes on initial presentation and were classified as skeletally mature. A total of 63 patients (28%) required surgical treatment for their knee injury. Overall, 50 anterior cruciate ligament (ACL) tears, 46 fractures, 39 meniscal tears, 31 ligamentous tears other than ACL, 22 patellar dislocations, and 38 soft tissue injuries, such as lacerations, were recorded. Skeletally mature patients had 7.8 times higher odds (95% CI, 1.6-46.8; P < .05) and 19.1 increased odds (95% CI, 5.5-74.9; P < .05) of an ACL tear or another ligamentous tear, respectively, compared with skeletally immature patients. Patients who described instability and giving way of the knee as relevant trauma mechanisms had odds of 3.11 (95% CI, 0.9-14.8; P < .05) of an ACL tear compared with other trauma mechanisms. Meniscal tears were observed more frequently in the skeletally mature cohort (P < .05). An elevated BMI was associated with a significantly higher relative risk of an ACL tear, a ligamentous tear other than the ACL, and an injury requiring surgery. A third of surgically treated patients were subject to a delayed diagnosis. - Conclusion: Adults had a significantly increased risk of ligamentous and meniscal tears and required operative intervention more often than skeletally immature individuals. Elevated BMI, age, and instability events in terms of trauma mechanism conveyed an increased risk of structural damage to the knee.
Gesehen am 06.05.2024